Evaluating H2BC9 as a potential diagnostic and prognostic biomarker in head and neck squamous cell carcinoma - Lanhua Wu; Liang Li; Mingjing Zhu; Ziyan Zhou; Xuejin Su; Yueming Jiang; Min Kang; Li Jiang (European Journal of Medical Research)
Abstract Background Histone H2B is highly expressed in many types of cancers and is involved in cancer development. H2B clustered histone 9 (H2BC9), a member of the H2B family, plays critical roles in gene expression regulation, chromosome structure, DNA repair stability, and cell cycle regulation. However, the diagnostic and prognostic value of H2BC9 in head and neck squamous cell carcinoma (HNSCC) remains unclear. This study aimed to evaluate the potential diagnostic and prognostic value of H2BC9 in HNSCC and investigate its biological role using bioinformatics. Methods The expression pattern and diagnostic value of H2BC9 in HNSCC were explored using UCSC Xena and GEO database. H2BC9 expression was validated using the Human Protein Atlas database, qRT-PCR, and western blotting. Prognostic value was assessed using Kaplan–Meier curves, Cox regression analysis, and a nomogram. Drug sensitivity was predicted using the R package pRRophetic, and molecular interactions were analyzed using the DepMap database. The impact of H2BC9 on HNSCC cells was further investigated through in vitro experiments. Results H2BC9 was markedly upregulated in HNSCC cell lines and tissues. High expression of H2BC9 was correlated with advanced-stage disease and poor prognosis. KEGG analysis linked H2BC9 to cell cycle regulation and DNA replication. H2BC9 expression influenced the drug sensitivity of paclitaxel, docetaxel, cisplatin, and 5-fluorouracil. Key molecules, such as TONSL, PITX2, NOTCH1, and H2BC10, were positively correlated with H2BC9 expression. Silencing H2BC9 suppressed cell proliferation, induced G2/M cell cycle arrest, and enhanced apoptosis and DNA damage in HNSCC cells. Conclusion We demonstrated that H2BC9 expression may be associated with HNSCC development and prognosis. These findings may provide a potential therapeutic target for HNSCC.